Tingkat Ekstrem Curah Hujan Pada Banjir Besar Sintang Tahun 2021 - Sutikno, Sutikno; Gusmayanti, Evi; Mulki, Gusti Zulkifli (Universitas Tanjungpura, 2025)
Floods for more than one month occurred in Sintang Regency from October to November 2021. Many people said it was an enormous flood in the last 40 years. Rainfall is one of the main factors that trigger floods. The data used in this study is Sintang rainfall from 1985 to 2021, Melawi rainfall from 1985 to 2021, and Kapuas Hulu rainfall from 1995 to 2021. If the rain occurred during the flood period is the highest since 1985, then the rainfall factor is presumed to have a significant role in triggering great floods in Sintang. If the rainfall that occurs is not the highest, then other environmental factors must have evaluated and repaired soon. The extreme rainfall data is calculated and compared with four selected data from 1985 to 2021. The extreme level of rainfall uses fixed values such as daily, ten-days, and monthly rainfall above 50mm, 150mm, and 300mm each in sequence. Unfixed values use the 95th percentile (P95) to the 99th percentile (P99) in the series data of each location. The P99 value was reached on daily and 3-day rainfall accumulation in Sintang and Melawi. The Monthly time scale was reached in Sintang on October 2021. Based on the score and ranking, rainfall accumulation in Sintang from October to November 2021 was ranked 3rd, Melawi was 2nd, and Kapuas Hulu was 3rd. It means rainfall from October to November 2021 is not the highest since 1985.